Influence of Work Motivation, Workload, and Job Stress on Volunteer Performance at the Adzkia Nugraha Nutrition Fulfillment Service Unit in Madiun Regency - Yonathan Febriyan Hartoyo; Muhammad Imron; Hartirini Warnaningtyas (Citakonsultindo, 2026)
Volunteer performance is crucial for the success of social and humanitarian organizations, yet maintaining their consistency poses a unique challenge compared to paid employees. While previous studies have extensively examined human resource factors in profit-oriented sectors, empirical evidence regarding the predictors of volunteer performance remains sketchy. Therefore, this study examines the predictive role of work motivation, workload, and job stress on volunteer performance at the Adzkia Nugraha Nutrition Fulfillment Service Unit (SPPG) in Madiun Regency. A quantitative research design was adopted, and data were collected from 132 participants selected using the Slovin formula. Data were analyzed using multiple linear regression, incorporating partial (t-test) and simultaneous (F-test) evaluations. The results demonstrated that work motivation partially had a positive and significant effect on volunteer performance. Conversely, workload and job stress showed a significant negative effect on performance. Furthermore, the simultaneous evaluation revealed that work motivation, workload, and job stress collectively significantly predicted volunteer performance. The model accounted for 39.2% of the variance in volunteer performance (Adjusted R2 = .392). The study concludes that intrinsic work motivation is the primary driver of volunteer performance, whereas excessive workload and high stress significantly hinder their contributions even in this specific non-profit context. The study recommends that organizational stakeholders focus on strategies that foster volunteer motivation, such as non-financial appreciation, to sustain service effectiveness. the primary driver of volunteer performance, whereas workload and stress do not significantly hinder their contributions.